Analisis Pengaruh Kalori Batubara dan Excess Air Pada Boiler CFB Dengan Metode CFD (Ansys) - Erwald Mataufani, Caesariski; Sidiq, Abdurahim; Arifin, Jainal (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The Pulang Pisau Steam Power Plant (PLTU) uses a CFB type boiler with a coal consumption of 4,054-5,260 kCal/kg. This research was carried out by modeling the CFB type boiler used in the Pulang Pisau PLTU using Autodesk Inventor 2021 then for the iteration process using Ansys Fluent 2022 R2, the excess air variation used is 5%, 10%, 15%, 20%, and 25%. Based on the results of iteration using Ansys Fluent 2022 R2 with 4,054-5,260 kCal/kg calorie coal, for the addition of 5% excess air, the temperature at the outlet furnace is 2,199°C, for the addition of 10% excess air, the temperature at the outlet furnace is 2,195°C , for the addition of 15% excess air, the temperature at the outlet furnace is 1,960°C, for the addition of 20% excess air, the temperature at the outlet furnace is 1,910°C, for the addition of 25% excess air, the temperature at the outlet furnace is 1,855°C, then it can be concluded that the final temperature at the boiler furnace outlet is still far from the set target of 840-850°C. Where the lowest temperature is at 25% excess air with a value of 1855°C. So it can be concluded that the best excess air requirement and that is closest to the target is 25% excess air.